Differences in phytoplankton dynamics and community structure between a wet year and dry year in the Zhoucun Reservoir. Issue 3 (2nd July 2016) - Qiu, Xiaopeng; Huang, Tinglin; Zeng, Mingzheng
Abstract : Rainfall-induced nutrient fluctuations in surface water affect phytoplankton communities and cause algal blooms. To examine this influence in the Zhoucun Reservoir, China, field surveys were performed weekly or biweekly from February 2013 (a wet year) to December 2014 (a dry year). Physical conditions, nutrient levels, and phytoplankton functional groups were investigated during monitoring. Nutrient levels increased in the summer of 2013 (TN: 0.85–2.66 mg/L; TP: 0.037–0.138 mg/L), while nitrogen deficiency occurred in the summer of 2014 (TN: 0.38–0.73 mg/L, TP: 0.044–0.079 mg/L). A cyanobacteria bloom that appeared in the summer of 2013 had the dominant phytoplankton functional groups M and Tc. In the summer of 2014, algal cell density and biomass were much lower than those during the corresponding period in 2013, and the co-dominant phytoplankton groups were F, L0, Tc, and S2. Non-N-fixing cyanobacteria were not abundant in summer 2013 probably because of the low ratio of NO3 − to NH4 +, although nitrogen was also deficient. In contrast to these summer trends, little difference was noted between phytoplankton dynamics and community structure in the two winters and two springs, regardless of nutrient conditions. Redundancy analysis indicated that rainfall-induced nitrogen fluctuations were the primary factor causing phytoplankton dynamics to differ between the wet and dry year. The effects of water temperature, stratification, and light on the phytoplankton community were independent of nutrient fluctuations. This study shows that rainfall fluctuations change summer nutrient conditions and that cyanobacteria blooms are likely to occur in wet years in the Zhoucun Reservoir.